2021
DOI: 10.2139/ssrn.3786062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the competitiveness of agricultural holdings in Bulgaria

Abstract: The problem of determining the competitiveness of various economic organizations is among the most topical academic and practical issues from the emergence of economics science to the present day. It is particularly important for the agricultural sector, which is characterized by many participants, high specialization and exchange, strong competition at local, national and international level, highly integrated food and supply chains, market segmentation, unequal public support, strong state regulation, proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The provision of skilled labor is problematic not only for different sectors of agricultural production, but also for the entire agriculture. The results of a questionnaire study, conducted by Bashev and Koteva (2022), show that a significant part of farms in the country have serious problems in effectively providing the necessary labor force. Popescu et al (2021) indicated that Bulgaria is among the countries that remain below the EU average for agricultural output per AWU in 2020.…”
Section: Sources: Fadn Own Calculations Figure 2 Input`s Index By Sec...mentioning
confidence: 99%
“…The provision of skilled labor is problematic not only for different sectors of agricultural production, but also for the entire agriculture. The results of a questionnaire study, conducted by Bashev and Koteva (2022), show that a significant part of farms in the country have serious problems in effectively providing the necessary labor force. Popescu et al (2021) indicated that Bulgaria is among the countries that remain below the EU average for agricultural output per AWU in 2020.…”
Section: Sources: Fadn Own Calculations Figure 2 Input`s Index By Sec...mentioning
confidence: 99%